Влияние тренировки на скорость возвращения деревенских ласточек к гнезду в экспериментах по «хомингу» - Смогоржевский, Л.А. (Вестник зоологии, 1974)
On the basis of the carried «hominp experiments with Hirundo rustica L. a conclusion is made that the trained birds on the whole return more quickly than untrained or less trained ones. At the same time the primary direction of the birds' flight at the first kilo¬meters of the way differs in the first and repeated letting out. It testifies to the fact that the swallows do not «memorize» the primary route of the flight but train their navigatory ability.